Use of Android-Based Media Benime Whiteboard Animation in Learning to Write Procedure Text in Vocational High School Students - Muthiani Agustine; Euis Eti Rohaeti; Rochmat Tri Sudrajat (JLER (Journal of Language Education Research), 2023)
In the era of the Industrial Revolution 4.0, students are a generation that is very close to the touch of technology. Therefore, teachers can not only rely on traditional-based media, but can also take advantage of technology-based media that are packaged attractively, creatively, and innovatively in order to achieve learning competencies. The purpose of this research is to develop teaching materials in the form of Â the Benime White Board Animation android application Â that can be accessed through student devices. This study also aims to determine the influence of android-based learning media on students' ability to determine the structure and linguistic characteristics of procedural texts. This study uses the R&D (Research and Development) methodÂ  which describes data on the Â influence of Benime White Board Animation's android-based learning media Â on students' ability to write procedure texts. The subjects in this study were 36 grade XI students of SMKN 1 Soreang. Data collection was carried out by observation, interviews, and questionnaires. After research, The Benime White Board Animation android applicationÂ  was successfully developed so that it can be accessed flexibly. In addition, the quality of this application is rated very decent / very good based on the average score carried out by validators, which is 85.59%. Each assessment was a media expert 83.77%, a material expert 85.00%, and a teacher Indonesian 88.00%. Then, students responded to the application during the trial by giving an excellent rating of 87.24%. Therefore, the Benime White Board Animation Â application has implications for learning that can be used as teaching materials so that it can improve writing skills, especially procedure texts.